Surgery with arterial resection for hilar cholangiocarcinoma: protocol for a systematic review and meta-analysis - Gomes dos Santos Ferreira Rebelo, Artur Luis; Ukkat, Jörg; Klose, Johannes; Ronellenfitsch, Ulrich; Kleeff, Jörg H. (JMIR Research Protocols, 2021)
arterial resection; cancer; cardiology; cholangiocarcinoma; liver; liver cancer; meta-analysis; morbidity; mortality; outcomes; perioperative; surgery; tumor; vascular resections